Sosialisasi Edukasi Tajhizul Mayit di Desa Hutabaringin Julu - Nur Maida Sari; M. Akbar Maulana; Ismi Zakiyah Dly; Nur Hamidah Dly; Yuspa Yuspa; Eva Suryani; Fitri Maharani Siagian; Irda Auliah; Meliana Meliana; Ahmad Tohir Husein; Darman Rangkuti (Lembaga Pengembangan Kinerja Dosen, 2025)
The educational outreach program for the handling of corpses (tajhizul mayit) conducted by Group 29 of the STAIN Madina Community Service Program in Hutabaringin Julu Village aimed to provide theoretical and practical understanding to the community regarding the procedures for handling corpses in accordance with Islamic law. Participants included mothers, fathers, and young men and women, who were expected to disseminate this knowledge to the wider community. This study used a qualitative descriptive approach with a participatory method, allowing participants to be directly involved in the learning process. The implementation of the activity included several methods, such as lectures given by expert speakers, live demonstrations on corpse handling procedures, corpse handling simulations, and discussions that actively involved participants. This activity was designed so that participants not only understood the theory but also had practical skills in handling corpses in accordance with Islamic teachings. The results of this activity showed a significant increase in participants' understanding and skills in handling corpses. In addition to increasing religious literacy, this activity also fostered collective awareness regarding the importance of fardhu kifayah obligations, which are a shared responsibility of the community. It is hoped that through this activity, the community will be better educated and better prepared to carry out religious duties properly.